Pengaruh Bauran Pemasaran Terhadap Kepuasan Konsumen (Studi Kasus Pada Produk Minuman Merek Teh Kotak Di Alfamart) - Syafruddin, Muhammad; Muchlis, Azizah (Jurnal Ilmiah Bongaya, 2022)
This research wants to know what. The Influence of Assets Grows, Liabilities Grow And Revenues Smooth Income So Reponse In Manufacturing Sector Companies Are Many In Place Bei Period 2018-2020. Data collection data results or quantitative data from the Financial data of the Indonesia Stock Exchange sector producing food and beverages totaling 33 tersoal. The results of the data have been tested classic assumptions in the form of assumptions of Normality, assumptions multicolinearity and heteroskedastisitas. The data analysis method uses multiepleregeression techniques.According to results the analiysis, it turns out that tha result optha studishoueddhat the first hypothesis wus accepted because it showed the results of the hypothesis test there was a significant positive influence. Means Asset growth contributes significantly to earning response.Means Asset growth contributes significantly to earning response. The second hypothesis was rejected because it showed the negative hypothesis test results were insignificant. Means Liabilities growth contributes unreal to earning response. The third hypothesis was rejected because Income smoothing had no significant negative effect. Income smoothing contributes unreal to earning response